Influence Existence of Oil Palm Plantations to Community Income (Case Study in Telaga Village Subdistrict Popayato Regency Pohuwato) - Santoso, Ivan Rahmat; Olilingo, Fahrudin Zain; Rauf, Alim (Journal of Business Management and Economic Development, 2023)
Study This For know enhancement income the people of Telaga Village, District Popayato, Regency Pohuwato, before and after existence plantation coconut palm oil PT Loka Indah Lestari. Study use approach quantitative with method ex post facto. Data collection obtained from results observation, questionnaire and documentation. The results of data analysis using analysis of Paired Samples t Test. Research Results showing that existence plantation coconut palm especially PT. Loka Indah Lestari is influential positive significant to income the people of Telaga Village District Popayato Regency Pohuwato. This show that existence plantation coconut PT. Loka Indah Lestari can for give benefit in stimulate absorption power implicated work Good in increase income society. Results per indicator found that plantation coconut palm especially by PT. Loka Indah Lestari is influential positive significant to income the people of Telaga Village District Popayato Regency Pohuwato, both on income personal, income disposable as well as income House stairs. However thus, results enhancement income public This must accompanied with awareness rehabilitation active environment done by society and company for continuity farming palm from aspect ecological, institutional, and social economy society.